Cell-penetrating peptides selectively targeting SMAD3 inhibit profibrotic TGF-β signaling - Kang, Jeong-Han (J Clin Invest, 2017)
TGF-β is considered a master switch in the pathogenesis of organ fibrosis. The primary mediators of this activity are the SMAD proteins, particularly SMAD3. In the current study, we have developed a cell-penetrating peptide (CPP) conjugate of the HIV TAT protein that is fused to an aminoterminal sequence of sorting nexin 9 (SNX9), which was previously shown to bind phosphorylated SMAD3 (pSMAD3). We determined that specifically preventing the nuclear import of pSMAD3 using the TAT-SNX9 peptide inhibited profibrotic TGF-β activity in murine cells and human lung fibroblasts as well as in vivo with no demonstrable toxicity. TGF-β signaling mediated by pSMAD2, bone morphogenetic protein 4 (BMP4), EGF, or PDGF was unaffected by the TAT-SNX9 peptide. Furthermore, while the TAT-SNX9 peptide prevented TGF-β’s profibrotic activity in vitro as well as in 2 murine treatment models of pulmonary fibrosis, a 3–amino acid point mutant that was unable to bind pSMAD3 proved ineffective. These findings indicate that specifically targeting pSMAD3 can ameliorate both the direct and indirect fibroproliferative actions of TGF-β.